2001
DOI: 10.1046/j.1537-2995.2001.41070878.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of HBV infection after blood transfusion in Japan through investigation of a comprehensive donor specimen repository

Abstract: The remaining risk of transfusion transmission of HBV infection before the adoption of NAT was mainly due to window-period donations, including one that was made before the HBV genome was detectable by PCR. However, it was determined that transfusion was not responsible in many cases for HBV infection after transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
74
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 21 publications
3
74
0
Order By: Relevance
“…In some countries such as Germany, Austria and Japan, blood units with antiHBs levels greater than 100 IU/L is considered to be safe [26]. However, there was evidence that transmission of HBV from occult hepatitis B subjects occurred in the presence of concurrent neutralizing anti-HBs in the same specimen [28]. Detection of HBV DNA in some anti-HBspositive samples in this study indicates that the absence of HBsAg and the presence of anti-HBs do not totally reflect the safety of blood donations.…”
Section: Discussionmentioning
confidence: 99%
“…In some countries such as Germany, Austria and Japan, blood units with antiHBs levels greater than 100 IU/L is considered to be safe [26]. However, there was evidence that transmission of HBV from occult hepatitis B subjects occurred in the presence of concurrent neutralizing anti-HBs in the same specimen [28]. Detection of HBV DNA in some anti-HBspositive samples in this study indicates that the absence of HBsAg and the presence of anti-HBs do not totally reflect the safety of blood donations.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 However, if this strategy is applied in the studied population, the use of anti-HBc would result in the disposal of 36.2% of blood units, with 42.6% of them might actually be safe. The anti-HBs titers in the HBsAg-negative/anti-HBc-positive samples did not illustrate the absence of viral infection, as 65.8% of anti-HBc-/anti-HBs-positive OHB cases showed antiHBs titers of > 100 IU/L (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…4 Whether HBsAg-negative/anti-HBc-positive units can transmit HBV infection to recipients is debated. [13][14][15][16][17][25][26][27] The low viremic content and often the concomitant presence of neutralizing anti-HBs antibodies has led several authors to conclude that blood from anti-HBc/anti-HBs-positive donors is safe; the English experience seems reassuring as no case of hepatitis B transmission was related to transfusion in a survey of 20000 blood units controlled only for HBsAg. 25 However, the prevalence of HBV is very low in Northern Europe and the number of units traced was relatively small, while the transfusion risk may be different in areas such as Italy, where HBV remains endemic.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of sensitive assays to detect HBV-DNA it was shown that healthy HBsAg-negative donors who have antibodies to HBV core antigen (antiHBc) may harbor an occult HBV infection and maintain HBV-DNA sequences in their liver and blood, thus representing potential sources of HBV transmission. [6][7][8][9][10][11][12][13][14][15][16][17] AntiHBc screening of blood donations is controversial and variably performed in different countries. Currently it is limited to areas where the seroprevalence of HBV is low (generally <2%), while it is not performed in areas with a high HBV seroprevalence because the impact of the deferral of anti-HBc-positive donors is considered not sustainable.…”
mentioning
confidence: 99%
See 1 more Smart Citation